Chromosomes of Crossopriza lyoni (Blackwall 1867), intraindividual numerical chromosome variation in Physocyclus globosus (Taczanowski 1874), and the distribution pattern of NORs (Araneomorphae, Haplogynae, Pholcidae) - Oliveira, Rosângela Martins [UNESP]; De Jesus, Aline Carolina [UNESP]; Brescovit, Antonio Domingues; Cella, Doralice Maria [UNESP] (American Arachnological Society, 2007)
Pholcidae (Haplogynae) encompasses 967 described species, of which only 14 have been cytogenetic analyzed. Several chromosomal features have already been described including presence of meta- and sub-metacentric chromosomes and sex determination chromosome system (SDCS) of the X, X1X2Y, and X1X2 types, which contrast with the telo- and acrocentric chromosomes and SDCS of the X1X2 type typical of entelegyne spiders. To obtain further cytogenetic information for the family, we examined two pholcid species, Crossopriza lyoni (Blackwall 1867) and Physocyclus globosus (Taczanowski 1874) using both conventional staining and silver staining techniques. Crossopriza lyoni exhibited 2n = 23 = 22 + X in males and 2n = 24 = 22 + XX in females, while P. globosus showed 2n = 15 = 14 + X and 4n = 30 = 28 + 2X, both in male adults, 2n = 16 = 14 + XX in female adults and embryos, and 2n = 15 = 14 + X in male embryos. Both species revealed predominately metacentric and submetacentric chromosomes and a SDCS of the X/XX type. The cytogenetic data obtained in this work and those already recorded for C. lyoni indicate interpopulational and intraspecific numerical chromosome variation, suggesting the presence of chromosomal races or cytotypes in this species. The intraindividual numerical chromosome variation observed in male adult specimens of P. globosus may be explained by the presence of cytoplasmatic bridges between germ cells. The use of the silver staining technique to reveal the nucleolar organizer region (NOR) showed that chromosome pairs 4 and 6 and the X chromosome in C. lyoni are telomeric NOR-bearers, and that the chromosome pair 2 in P. globosus possesses a proximal NOR in the long arm.
Keywords: Chiasma; Chromosome rearrangements; Meiosis; Syncytial; Tetraploidy; Araneae; Araneomorphae; Crossopriza lyoni; Haplogynae; Pholcidae; Physocyclus globosus